Recreational drugs and its effects on sperm - Eghosa Enoriomwaniha (BioScientist: The Salford Biomedicine Society Magazine, 2024)
Recreational drugs are mainly used by young people and they are legal and illegal substances taken by individuals for pleasure rather than medical purposes. In England, the most used recreational drug is cannabis among other drugs including cocaine, codeine, ecstasy, alcohol, and nicotine. Recreational drugs can have a negative influence on men’s sperm by reducing its quality and having an impact on male hormones like testosterone which is necessary for the regulation of the male reproductive system. There are limited studies on the effects of recreational drugs on sperm but there is evidence that demonstrates the negative influence of these drugs on sperm and the male reproductive system. It also relates to health ethics and parental responsibility as it can have a negative impact on their future children leading to the importance of informing the public about the consequences of recreational drugs on the male reproductive system.
Keywords: recreational drugs; sperm; cannabis; cocaine; codeine; ecstasy; alcohol; nicotine; fertility; sperm quality; sperm concentration; sperm motility; spermatogenesis; testes; testicles; testosterone; male infertility; sperm production; semen parameters; seen quality; reproductive system; ethical issues